2018
DOI: 10.1111/dme.13786
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c values and hospital admissions in children and adolescents receiving continuous subcutaneous insulin infusion therapy

Abstract: Despite significant reductions in HbA levels for individuals treated with CSII, improvements are needed to reduce diabetic ketoacidosis hospitalizations for those new to the therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
6
0
3
Order By: Relevance
“…Furthermore, a recent comparative study by Karges et al (18) show that the use of CSII has better glycemic control during the most recent year of therapy. Similar results (19)(20)(21)(22) have also been reported in other randomized controlled clinical trials, comparing the results of CSII and MDI in the treatment of T1DM, in which the HbA1C in CSII group was improved. An analysis of mean daily insulin dose in both treatment groups showed significantly lower daily insulin requirements in CSII group after 1 and 4 years of treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, a recent comparative study by Karges et al (18) show that the use of CSII has better glycemic control during the most recent year of therapy. Similar results (19)(20)(21)(22) have also been reported in other randomized controlled clinical trials, comparing the results of CSII and MDI in the treatment of T1DM, in which the HbA1C in CSII group was improved. An analysis of mean daily insulin dose in both treatment groups showed significantly lower daily insulin requirements in CSII group after 1 and 4 years of treatment.…”
Section: Discussionsupporting
confidence: 86%
“…A major policy change to quickly increase provision of insulin pumps in Scotland was introduced in 2011, and initially was mostly targeted towards children [6]. Although a recent study in England and Wales did not suggest any benefit in HbA 1c reduction with insulin pumps compared with multiple daily insulin injections in children and adolescents [15], other studies have reported improvements [16]. Apart from insulin pump policies, the larger improvement in children may have reflected other differences in services between paediatrics and adult clinics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found no benefit to the use of these technologies and have also identified increased rates of diabetic ketoacidosis (DKA) in pump users. [8][9][10][11] However, other studies have shown improvements in glycemic control and health-related quality of life while simultaneously reducing the incidence of severe hypoglycemia and DKA. 5,[12][13][14][15][16] Despite increasing use of these technologies in clinical practice, the average A1c among patients <26 years of age in the T1DX is not improving.…”
Section: Introductionmentioning
confidence: 99%